2020
DOI: 10.12688/wellcomeopenres.16351.1
|View full text |Cite
|
Sign up to set email alerts
|

The ethics of data sharing and biobanking in health research

Abstract: The importance of data sharing and biobanking are increasingly being recognised in global health research. Such practices are perceived to have the potential to promote science by maximising the utility of data and samples. However, they also raise ethical challenges which can be exacerbated by existing disparities in power, infrastructure and capacity. The Global Forum on Bioethics in Research (GFBR) convened in Stellenbosch, South Africa in November 2018, to explore the ethics of data sharing and biobanking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 9 publications
(7 reference statements)
1
18
0
Order By: Relevance
“… 19 53 Where this was not possible, stakeholders concluded that benefits should at least be shared with originating communities by making the results of secondary analyses available to local researchers, communities and health ministries. 58 60 63 Some community representatives were supportive of health benefits accruing to the wider public, rather than directly back to their communities. 19 This was in recognition of the fact that health research data, especially when publicly funded, constitutes a public good.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 53 Where this was not possible, stakeholders concluded that benefits should at least be shared with originating communities by making the results of secondary analyses available to local researchers, communities and health ministries. 58 60 63 Some community representatives were supportive of health benefits accruing to the wider public, rather than directly back to their communities. 19 This was in recognition of the fact that health research data, especially when publicly funded, constitutes a public good.…”
Section: Resultsmentioning
confidence: 99%
“…31 50 51 62 63 In some LMIC settings, there is a lack of robust regulatory and governance structures to support equitable data sharing. 58 Existing ethical frameworks and case studies were thought to primarily address HIC contexts and did not reflect the difficulties LMIC researchers faced. 53 A lack of enforceable agreements leaves LMIC researchers exposed to exploitation and fails to safeguard participants from harms.…”
Section: Bmj Globalmentioning
confidence: 99%
“…Attitudes regarding engaging the community in the practices of a biobank. identified by others as challenges for biobank research in LMICs (Barchi et al, 2015;Bull and Bhagwandin, 2020;Ezzat et al, 2022;Nansumba et al, 2019;Yakubu et al, 2018). Bull and Bhagwandin (2020) maintain that failure to provide participants with necessary information regarding genetic research threatens the protection of participants, fails to respect persons, and can compromise trust in relationships.…”
Section: Discussionmentioning
confidence: 99%
“…identified by others as challenges for biobank research in LMICs (Barchi et al, 2015;Bull and Bhagwandin, 2020;Ezzat et al, 2022;Nansumba et al, 2019;Yakubu et al, 2018). Bull and Bhagwandin (2020) maintain that failure to provide participants with necessary information regarding genetic research threatens the protection of participants, fails to respect persons, and can compromise trust in relationships. Regarding the significance of trust, Ngwenya et al (2020) concluded that participation in biobank research is based on trust, regardless of the purposes of the study, especially in communities with high rates of poverty and illiteracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation